A identidade do eu pós-convencional e os diversos sentidos da metamorfose: a história de José Junior - Pflaeging, Patrícia Sampaio (2009)
The goal of the present dissertation is to investigate the construction of the post-conventional identity of the Self, proposed by Habermas, as well as understand how the post-conventional identity leads with the fetish of the character. In this context, we aimed to analyse how the post-conventional person builds his multiples characters, leads with collective roles and maintains his autonomy in order to articulate a new life project. For this purpose we used the Social Psychology and the concept of identity-metamorphosis-emancipation, developed by Ciampa, as the main category of analysis, considering to understand not only the phenomenon in its instrumental aspect, but, also the context in which the individual is placed. The research was carried through from the narrative of the participant life history, focusing different moments of his path. This dissertation presents some considerations on in order to offers subsidies to discuss the post-conventional identity of the Self, his possibilities of emancipation and the various meanings of metamorphosis